Production and Distribution System of Literary Books in Parist Penerbit: A Sociology of Literature Analysis - Lestari, Dewi; Falah, Fajrul (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
The book publishing industry continues to evolve in response market trends and demands. This evolution has gradually turned literature into economic commodities and affects the variety of books in the market. Parist Penerbit, as one of the local publishers in Kudus, also faces these dynamics. Parist Penerbit is under the auspices of the Paradigma Institute. This research aims to identify Parist Penerbit's production and distribution system. The research was conducted using a sociology of literature approach to examine the production and distribution system of Parist Penerbit. The research method involved field studies through in-depth interviews and literature studies. The results show that Parist Penerbit's book production system is influenced by various factors, such as the editor-in-chief's decision, market demand, and agreement among Paradigma Institute members. The selection of themes, genres, and quality of books is influenced by the publisher's strategy, especially the role of the editor-in-chief. Market demand influences the editor-in-chief's decision to accept manuscripts. Paradigma Institute also has its own standards and criteria for its books. Parist Penerbit tries to maintain its existence with various strategies, such as organizing book discussions and selling book online. This research provides an in-depth understanding of Parist Penerbit's production and distribution system.
Keywords: Book Publishing, Literature, Robert Escarpit, Book Production, Sociology of Literature